Experimental Characterisation and Field Experience of a Reusable, Modified Polyurethane Foam for the Mechanical Clean-Up of Oil Spills on the Sea Surface - Daniel Niehaus; Sebastian Hofmann; Srividya Bairamangala Kumar; Marko Hoffmann; Jesús Cisneros-Aguirre; Michael Schlüter (Journal of Marine Science and Engineering, 2022)
Oil spills at sea, such as the Deepwater Horizon incident in 2010, are devastating environmental hazards, especially for biodiversity in the maritime ecosystem. In order to help the restoration of coastlines, it is critical to clean the oil up quickly and efficiently with various measures, such as the use of barriers, skimmers, sorbents, dispersing agents, in situ burning, and biological agents. However, most of them still cause high remediation costs; are inefficient, non-reusable, and not environmentally friendly; lack a convenient desorption method; or are simply not yet ready to use in a real-case scenario, where high amounts of hydrocarbons must be removed. Therefore, in this work, a reusable modified polyurethane foam for oil absorption on the sea surface is presented and characterised. Due to a chemical formulation with a special co-polymer, its oleophilic properties are strongly enhanced. Laboratory soaking tests with different oils and a mixture of Louisiana sweet crude oil with artificial sea water (ASW) are conducted. To do so, a pneumatic press with adjustable pressures was used to characterise the foam’s capability to recover oil between 10 and 18 times its own weight for a period of up to 50 consecutive repetitions with a maximum saturation in less than one minute. Sequential trials with different oil mass fractions in ASW determined a decreasing content of recovered ASW with increasing amounts of crude oil, while, in all cases, the total oil recovery rate proved to be more than 90% within one’s standard deviation. Finally, practical applications of sorption methods are presented to give an idea of difficulties encountered in real remediation scenarios.